NGOs and the effectiveness of interventions - Faraz Usmani; Marc Jeuland; Subhrendu Pattanayak (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
Interventions led by non-governmental organizations (NGOs) are often more effective than comparable efforts by other actors, yet relatively little is known about how implementer identity drives final outcomes. Combining a stratified field experiment in India with a triple-differences estimation strategy, we show that a local development NGO's prior engagement with target communities increases the effectiveness of a technology-promotion intervention implemented by it by at least 30 percent. This "NGO effect" has implications for the generalizability and scalability of evidence from experimental research conducted with local implementation partners. – – Interventionen, die von Nichtregierungsorganisationen (NGOs) durchgeführt werden, sind oft effektiver als vergleichbare Projekte anderer Akteure, aber es ist relativ wenig darüber bekannt, wie die Identität der Durchführenden die Wirkungen der Intervention beeinflusst. Durch die Kombination eines geschichteten Feldexperiments in Indien mit einer Triple-Differenzen Schätzstrategie zeigen wir, dass das vorherige Engagement einer lokalen Entwicklungs-NGO in den Zielgemeinden die Effektivität einer von ihr durchgeführten Intervention zur Technologieförderung um mindestens 30 Prozent erhöht. Dieser "NGO-Effekt" hat Implikationen für die Verallgemeinerbarkeit und Skalierbarkeit von Erkenntnissen aus experimenteller Forschung, die mit lokalen Implementierungspartnern durchgeführt wurden.
Keywords: L31; C93; O12; O17; 330; NGOs; field experiments; external validity